Adapting the measurement of youth entrepreneurship potential in a marginalised context: the case of Mindanao, Philippines. (2017) - Lai, Cynthia; Dentoni, Domenico; Chan, Catherine; Neyra, Elma M.
Few studies have so far discussed how to measure youth entrepreneurship potential, a critical construct to enhance the success and performance outcomes of entrepreneurship education programs. This article investigates the adaptation of a measurement model of youth entrepreneurship potential, which a psychology strand of the extant entrepreneurship literature from the USA and Europe identified as characteristics of 'successful' future entrepreneurs. Two subsequent questionnaires were administered to measure youth entrepreneurship potential as part of an entrepreneurship education program in Mindanao, Philippines, a marginalised context. The first questionnaire had scales based on personality traits of autonomy, need for achievement, innovativeness and risk-taking propensity as per the extant literature, while the second had adapted scales to the local context. A confirmatory factor analysis tested the effectiveness of both measurement models. Results indicated that the locally adapted measurement model was more effective to assess youth entrepreneurship potential in the context of Mindanao, Philippines.